2016
DOI: 10.1109/tbcas.2016.2518923
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Electrocorticographic Spectral Characteristics for Optimized Signal Chain Design: A 1.08 W Analog Front End With Reduced ADC Resolution Requirements<formula formulatype="inline"> <tex Notation="TeX"/> </formula>

Abstract: Electrocorticography (ECoG) is an important area of research for Brain-Computer Interface (BCI) development. ECoG, along with some other biopotentials, has spectral characteristics that can be exploited for more optimal front-end performance than is achievable with conventional techniques. This paper optimizes noise performance of such a system and discusses an equalization technique that reduces the analog-to-digital converter (ADC) dynamic range requirements and eliminates the need for a variable gain amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This makes low frequency bands more tolerant to the aggregated noise contributed by biological tissue, electrodes and recording front-ends [39], [40]. Indeed, it has been shown that even with modest amplifier noise specifications, without suppressing flicker contributions, SNRs larger than 30 dB can be obtained at low frequencies [41]. This suggests that PS calculations can be relevant as a neurological biomarker in the β and lower frequency bands although the reliability decreases for the high-γ band and higher frequencies.…”
Section: Event-based Phase Synchronizationmentioning
confidence: 99%
“…This makes low frequency bands more tolerant to the aggregated noise contributed by biological tissue, electrodes and recording front-ends [39], [40]. Indeed, it has been shown that even with modest amplifier noise specifications, without suppressing flicker contributions, SNRs larger than 30 dB can be obtained at low frequencies [41]. This suggests that PS calculations can be relevant as a neurological biomarker in the β and lower frequency bands although the reliability decreases for the high-γ band and higher frequencies.…”
Section: Event-based Phase Synchronizationmentioning
confidence: 99%
“…Some of them obtain very low noise and low power performance [10], however they do not include methods to deal with the large DC offsets at the electrode-tissue interface. In other cases, the front-end exhibits low input impedance [4], high power consumption [8] or high input-referred noise [9].…”
Section: Introductionmentioning
confidence: 99%
“…An additional challenge is the high dynamic range associated with bio-potential measurements [4], [9], [12]- [14]. For instance, an electrocortical (ECoG) signal is usually sensed, as depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The most straightforward method of rejecting the electrode offset is by AC coupling, which performs passive high-pass filtering with a very low cut-off frequency [14], [21]- [23]. However, the total common-mode rejection is limited by the capacitor matching accuracy, which is further deteriorated by the impedance unbalance between the sensing and reference terminals of the analog front-end [24], [25].…”
Section: Introductionmentioning
confidence: 99%